Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/8597872
|View full text |Cite
|
Sign up to set email alerts
|

Concrescence: Cone-Beam Computed Tomography Imaging Perspective

Abstract: Concrescence is a form of twinning, formed by the confluence of cementum of two teeth at the root level. The diagnosis of concrescence has largely relied on the conventional 2D imaging. The 2D imaging has inherent limitations such as distortion and superimposition. Cone-Beam CT eliminates these limitations. The aim of this article was to describe a case of dental abnormality using Cone-Beam CT imaging modality. Volumetric data demonstrated confluence of left mandibular third molar with a paramolar, a supernume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The tomography and its beautiful images, 5,6 including 3D, have provided a very accurate diagnostic acuity and allow an accurate diagnosis of dental concrescence based on very precise conceptual and imaging criteria applicable to all specialties of human knowledge. [7][8][9][10]…”
Section: B Amentioning
confidence: 99%
“…The tomography and its beautiful images, 5,6 including 3D, have provided a very accurate diagnostic acuity and allow an accurate diagnosis of dental concrescence based on very precise conceptual and imaging criteria applicable to all specialties of human knowledge. [7][8][9][10]…”
Section: B Amentioning
confidence: 99%
“…16 Also, CBCT will best show cementum connection. 40 Dens invaginatus is an anomaly that occurs on teeth presenting calcified layers invaginated in the dental pulp, forming a new tooth inside the tooth itself. This condition usually occurs bilaterally, with the most affected tooth the maxillary lateral incisor.…”
Section: Anomalies In Shapementioning
confidence: 99%
“…Concrescence is a rare developmental dental alteration, which may be influenced by environmental factors in its etiology, such as trauma, infections, inflammatory reactions, among others (Neville, Damm, Allen &Chi, 2016 andSugiyama et al 2007). However, its etiology is still not fully understood (Syed, Alluri, Mallela &Frazee, 2016 andRomito, 2004). Its development can occur in two different stages: first during root formation, being classified as true concrescence, and after complete root formation, being denominated as acquired concrescence (Gunduz, Sumer, Sumer & Gunhan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown no predisposition for a particular ethnicity, age or gender (Syed et al 2016 andKardach, Sobieszczyk &Sokalski, 2016). And the incidence of concrescence in extracted teeth is 0.8% in permanent teeth and 0.2-4% in the deciduous dentition (Syed et al 2016 andForan, Komabayashi &Lin, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation